SISTEM ANGGARAN BERBASIS KINERJA PADA UNIVERSITAS MUHAMMADIYAH PAREPARE - Fatimah; Hasdiana; Arfianty; Mulia Mustika (Economos : Jurnal Ekonomi dan Bisnis, 2022)
Performance-based budgeting emphasizes more on the utilization of available funds to achieve optimal results. Performance-based budgeting is oriented toward organizational output and is closely related to the vision, mission, and strategic plans of the organization, for example, the University Muhammadiyah of Parepare, so this study aims to determine the implementation of a performance-based budgeting system at the University of Muhammadiyah Parepare. The data collection techniques used in this research are interviews, documentation, and observation. Informants in this study were the Head of the Bureau and several exchequers of the University of Muhammadiyah Parepare. The data analysis technique in this study used descriptive qualitative analysis. The implementation of performance-based budgeting at the University of Muhammadiyah Parepare has been going quite well. However, in the implementation of its activities there are still obstacles, such as the budget that has been planned but has not been realized. This budget is not only based on what is spent, as is the case in the traditional budget system, but is also based on certain objectives/plans whose implementation needs to be prepared or supported by an adequate budget and the use of these costs must be efficient and effective. The implementation of performance-based budgeting at the University of Muhammadiyah Parepare consists of four indicators, namely the planning/budget preparation stage, the budget implementation stage, the reporting and budget evaluation stages